Aerobic Exercise Training Selectively Changes Oxysterol Levels and Metabolism Reducing Cholesterol Accumulation in the Aorta of Dyslipidemic Mice - Ferreira, Guilherme Silva; Pinto, Paula R.; Iborra, Rodrigo T.; Del Bianco, Vanessa; Santana, Monique Fátima Mello; Nakandakare, Edna Regina; Nunes, Valéria S.; Negrão, Carlos E.; Catanozi, Sergio; Passarelli, Marisa (Frontiers in Physiology, 2017)
Background: Oxysterols are bioactive lipids that control cellular cholesterol synthesis, uptake, and exportation besides mediating inflammation and cytotoxicity that modulate the development of atherosclerosis. Aerobic exercise training (AET) prevents and regresses atherosclerosis by the improvement of lipid metabolism, reverse cholesterol transport (RCT) and antioxidant defenses in the arterial wall. We investigated in dyslipidemic mice the role of a 6-week AET program in the content of plasma and aortic arch cholesterol and oxysterols, the expression of genes related to cholesterol flux and the effect of the exercise-mimetic AICAR, an AMPK activator, in macrophage oxysterols concentration. Methods: Sixteen-week old male apo E KO mice fed a chow diet were included in the protocol. Animals were trained in a treadmill running, 15m/min, 5 days/week, for 60 min (T; n = 29). A control group was kept sedentary (S; n = 32). Plasma lipids and glucose were determined by enzymatic techniques and glucometer, respectively. Cholesterol and oxysterols in aortic arch and macrophages were measured by gas chromatography/mass spectrometry. The expression of genes involved in lipid metabolism was determined by RT-qPCR. The effect of AMPK in oxysterols metabolism was determined in J774 macrophages treated with 0.25 mM AICAR. Results: Body weight and plasma TC, TG, HDL-c, glucose, and oxysterols were similar between groups. As compared to S group, AET enhanced 7β-hydroxycholesterol (70%) and reduced cholesterol (32%) in aorta. In addition, exercise increased Cyp27a1 (54%), Cd36 (75%), Cat (70%), Prkaa1 (40%) and Prkaa2 (51%) mRNA. In macrophages, the activation of AMPK followed by incubation with HDL2 increased Abca1 (52%) and Cd36 (220%) and decrease Prkaα1 (19%), Cyp27a1 (47%) and 7α-hydroxycholesterol level. Conclusion: AET increases 7β-hydroxycholesterol in the aortic arch of dyslipidemic mice, which is related to the enhanced expression of Cd36. In addition, the increase and reduction of Cyp27a1 and Cyp7b1 in trained mice may contribute to enhance levels of 27-OH C. Both oxysterols may act as an alternative pathway for the RCT contributing to the reduction of cholesterol in the aortic arch preventing atherogenesis.